The Association of Alcohol Use Disorders with Suicidal Ideation and Suicide Attempts in a Population-Based Sample with Mood Symptoms. Issue 2 (2nd April 2016) - Sung, Yoon-kyu; La Flair, Lareina N.; Mojtabai, Ramin; Lee, Li-Ching; Spivak, Stanislav; Crum, Rosa M.
Abstract : Using population-based data, we examined associations between alcohol use disorders (AUD) and suicidality, assessing effect modification by mood disorders, and mediation by drinking level. Suicidality was assessed among current drinkers with 2-weeks of low mood (n = 9, 173) in the National Epidemiologic Survey on Alcohol and Related Conditions. Independent of mood disorder, alcohol dependence, was associated with suicidal ideation (adjusted odds ratio [AOR] = 1.64; 95% confidence interval [CI] = 1.25–2.14), and suicide attempts (AOR = 2.02; CI = 1.43–2.85) relative to those without AUD. Findings indicate partial mediation by consumption. Associations between AUD and suicidality among those with low mood are not explained by comorbid mood disorder, but are partially mediated by drinking level. Future studies should evaluate transitions in suicidality with change in consumption.